Cross‐cultural validation of the Children's Assessment of Participation and Enjoyment (CAPE) in Spain. Issue 2 (5th December 2012) - Longo, E.; Badia, M.; Orgaz, B.; Verdugo, M. A.
Abstract Background Despite growing interest in the topic of participation, the construct has not yet been assessed in children and adolescents with and without cerebral palsy (CP) in Spain. As there are no available instruments to measure participation in leisure activities which have been adapted in this country, the goal of this study was to validate a Spanish version of the Children's Assessment of Participation and Enjoyment (CAPE). Method The sample comprised 199 children and adolescents with CP and 199 without CP, between 8 and 18 years of age, from seven regions in Spain. The adaptation of the original version of CAPE was carried out through translation and backward translation, and the validity of the instrument was analysed. Construct validity was assessed through the correlation of the diverse CAPE domains and the quality of life domains (KIDSCREEN questionnaire). Discriminant validity was established by comparing children and adolescents with CP and typically developing children and adolescents. For test–retest reliability, the children and adolescents with and without CP completed the CAPE questionnaire twice within 4 weeks. Results The correlations found between the CAPE domains and the quality of life domains show that the CAPE presents construct validity. The CAPE discriminated children and adolescents with CP from those without any disability in the results of participation. According to most CAPE domains, typically developing children and adolescents engage in a greater number of activities than children and adolescents with CP. Test–retest reliability for the Spanish version of CAPE was adequate. Conclusion The study provides a valid instrument to assess the participation of children and adolescents with and without CP who live in Spain.